Adolescents Harassment and Rape: A Study of Teenage Abusers and Rapist in the Banda Aceh Detention Center - Hetti Zuliani; Abu Bakar; Miftah Farhani (Proceedings of AICS - Social Sciences, 2018)
More and more sexual harassment rates are taking place in various regions around the world including in Aceh. Based on these conditions, the study was aimed to examine the causes of sexual behavior deviation in the teenage harassers and rapist. The purpose of the study was to find out the characteristics of abusers and rapist, the causes of harassment and rape and the psychological impact on the offender. The research approach used was qualitative with the method of case study. The sample size was 5 inmates at Banda Aceh Detention Center. The data collecting methods employed interviews, observation, and documentation. Data processing techniques applied was data reduction, display data and conclusion drawing. The results showed three characteristics of abuser: (1) low education level (2) lack of socialization in society (3) people closest to the victim. The causes of harassment and rape are due to (1) opportunities and (2) uncontrollable sexual desires. Lastly, psychological impact felt by the perpetrator is shame, deep regret, depressed with society and family view.Keywords:sexual behavior deviation, teenage sexual abuser, teenage rapist.